Otimização técnico-econômica de espessuras de paredes de dutos sanduíches - Bastos, Alexandre Paranhos (2018)
In this work, the outflow of oil production by underwater pipelines is of major importance within the supply chain in the oil industry. A relevant part of the investments in production is determined by the costs of the submarine lines, as these lines need to withstand the adverse conditions that are subjected to the great depths of the ocean. Projects of new types of pipelines that meet such adversities and minimize the high costs prove to be a very important objective for the feasibility of producing wells in ultra-deep waters. An alternative that has been studied is the so-called sandwich pipe, which is an evolution of PIP and theoretically presents superior mechanical and thermal performance. The surveys of the sandwich pipe are oriented in the definition of the materials and the design that provide a good relation between cost and performance. In this context, this work presents a mathematical model of non-linear programming that seeks to define the thicknesses of the layers of submarine pipes in function of their materials to minimize the cost of production of the sandwich pipe.